Silver Nanocoating of LiNi0.8Co0.1Mn0.1O2 Cathode Material for Lithium-Ion Batteries - Xintong Li; Kai Chang; Somia M. Abbas; Rasha S. El-Tawil; Ashraf E. Abdel-Ghany; Ahmed M. Hashem; Hua Wang; Amanda L. Coughlin; Shixiong Zhang; Alain Mauger; Likun Zhu; Christian M. Julien (Micromachines, 2023)
Surface coating has become an effective approach to improve the electrochemical performance of Ni-rich cathode materials. In this study, we investigated the nature of an Ag coating layer and its effect on electrochemical properties of the LiNi0.8Co0.1Mn0.1O2 (NCM811) cathode material, which was synthesized using 3 mol.% of silver nanoparticles by a facile, cost-effective, scalable and convenient method. We conducted structural analyses using X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy, which revealed that the Ag nanoparticle coating did not affect the layered structure of NCM811. The Ag-coated sample had less cation mixing compared to the pristine NMC811, which could be attributed to the surface protection of Ag coating from air contamination. The Ag-coated NCM811 exhibited better kinetics than the pristine one, which is attributed to the higher electronic conductivity and better layered structure provided by the Ag nanoparticle coating. The Ag-coated NCM811 delivered a discharge capacity of 185 mAh·g−1 at the first cycle and 120 mAh·g−1 at the 100th cycle, respectively, which is better than the pristine NMC811.